FAKTOR-FAKTOR YANG MEMPENGARUHI PERKAWINAN USIA MUDA PADA REMAJA PUTRI USIA 10-19 TAHUN DI KECAMATAN SELAKAU KABUPATEN SAMBAS - Aulia, Ayuning; Taufik, M; Hastuti, Lidia (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
Early marriage is a formal marriage or informal union entered into by an adolescent girl before reaching the age of 20. Based on the health, psychological, economic, and social aspects this age is considered too early to get married. From 2011 to 2013, Kecamatan Selakau, Kabupaten Sambas contributed the highest number of fertile couples. There were 1826 (0.06%) fertile couples in 2011, 1743 (0.05%) fertile couples in 2012, and 1759 (0.05%) fertile couples in 2013. The study aimed at identifying the influential factors of early marriage in adolescent girls aged 10-19 in Kecamatan Selakau, kabupaten Sambas.Using case control design, this study employed 44 samples (22 samples of case group and 22 samples of control group). The samples were selected by using purposive sampling technique. The test used was chi square test, with 95% confidence level. The study revealed that there were significant correlation of education (p value= 0,021, OR= 12,000, 95% CI= 1,348-106,803), motivation to continue study (p value= 0,000, OR= 16,889, 95% CI= 3,631-78,560), porn media (p value= 0,001, OR= 12,000, 95% CI= 2,862-50,306), knowledge (p value= 0,032, OR= 4,911, 95% CI= 1,325-18,205), and early marriage. On the other hand, the variable that didn’t correlate with early marriage was parent’s income (p value= 1,000, OR= 0,633, 95% CI= 0,095-4,218).From the findings, to reduce the early marriage cases, National Family Planning Coordinating Board of West Kalimantan is encouraged to provide both adolescent girls and parents information about reproductive health.Key words : Early marriage, Adolescents, Education, Knowledge, Porn media